CLIMATE RESILIENT TECHNOLOGY ADAPTATION AND EXPECTED COST OF UNCERTAINTY UNDER NAGARJUNA SAGAR PROJECT, KRISHNA RIVER BASIN - M. CHANDRASEKHAR REDDY, D. VISHNU SHANKAR RAO, G. RAGHUNADHA REDDY, K. GURAVA REDDY AND V. SREENIVASA RAO (The Journal of Research ANGRAU, 2016)
Policy makers are figuring out on the upscaling of the adaptation technologies with the changing climate.Adaptation strategies followed by the farmers is very low and had ranged from 6-30 percent only. This is mainly dueto the lack of awareness about the actual cost associated with adaption and non-adaptation strategies. Hence, thepresent papers address the cost of adaptation for rice using joint probability distribution of rainfall and crop prices. Thecost of adaptation varied from Rs.3520 to Rs.646 ha-1 for the adaptation of direct seeding of rice, modified system ofrice intensification and alternate wetting and drying of rice, whereas, the expected cost for not using the se technologiesrange from Rs.1900 to Rs.12423 ha-1. It was found out from the study that promotion of adaptation technologies itselfminimize the income losses to the farmers to a large extent.